Assistance rendered by Sri Lanka for the development of the Pāli Literature - Thero, Rev. Udugama Saranathissa (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 3 No 1 (2020): ปีที่ 3 ฉบับที่ 1 ประจำเดือนมกราคม - มิถุนายน 2563, 2020)
The Lord Buddha who showed the path to get over the suffering of existence and expounded the doctrines for forty-five years and such preaching was expounded using the language we accept today, as the Pāli language.             In the Buddhist canon, the Tripitaka, the following literature wascompiled together in the language recognized as Pāli. Yet during the time of Tıka or during the period of writing the explanation, the Buddhist language (the present Pāli language) was used to wield by the sonance of the thantibhāsā or language. MāgadhıBhāsā or the language of the Magadha country. But, it is quite visible that the Pāli sound rendered different meanings when using it in Atuwā, explanation and in the Tıkā, further explanations or demonstrations.